Silicon Photoanode Modified with Work‐function‐tuned Ni@FeyNi1−y(OH)2 Core‐Shell Particles for Water Oxidation. Issue 22 (16th October 2020) - Liu, Duanduan; Jiang, Tong; Liu, Depei; Zhang, Weining; Qin, Hao; Yan, Shicheng; Zou, Zhigang
Abstract: The photoelectrochemical (PEC) water splitting determines by the light absorption and charge extraction/injection. Here, we dispersedly modified the core‐shell structured Ni@Ni y Fe1− y (OH)2 on Si photoanodes and in‐situ electrochemically converted it to Ni@Ni y Fe1− y OOH to form a Si/SiO x /Ni@Ni y Fe1− y OOH assembly, exhibiting the adjustable band bending and catalytic ability in water oxidation depending closely on the composition of Ni y Fe1− y OOH. Combining with the island‐like dispersed distribution to maximize the light absorption and the Ni@Ni y Fe1− y shell as a high work function and a catalytic layer to simultaneously enlarge charge extraction and injection, the Si/SiO x /Ni@Ni0.7 Fe0.3 OOH assembly achieved an onset potential of 1.0 VRHE, a saturated current density of 35.4 mA cm −2 and a more than 50 h stability in an electrolyte with pH 9 under AM1.5G simulated sunlight irradiation. Our findings suggested that regulating the charge energetics at Si‐electrolyte interface by discontinuously modifying a composition‐adjustable core‐shell structure is a potential route to develop highly efficient PEC devices. Abstract : Shell tuning : The core‐shell structured Si/SiO x /Ni@Ni y Fe1− y (OH)2 photoanode is tuned by its adjustable composition of the Ni@Ni y Fe1− y OOH shell to enhance the photoelectrochemical performance.